Strategi Komunikasi Public Relations Aston Imperium Hotel dalam Mempertahankan Kearifan Lokal di Era 4.0 - Sefy Andhriany (Jurnal Ilmiah Komunikasi Makna, 2021)
Preserving local culture by reflecting it in every organization's activities becomes a challenge for Public Relations in the digital era 4.0. This is due to a shift in local culture which was replaced by foreign cultures that entered Indonesia. Various kinds of communication strategies are carried out, one of them is by the Public Relations of Aston Imperium Purwokerto hotel which maintains the local cultural specialties at the hotel. This study aims to analyze the communication strategy carried out by Aston Imperium Hotel Public Relations in maintaining local diversity in the 4.0 era. This study uses qualitative research methods with data collection techniques through in-depth interviews, observation, and related literature studies. The results of this study indicate that the Aston Imperium Hotel Public Relations communication strategy is implemented internally and externally. Internally, local culture is included in the forms of food and beverage, Banyumas regional specialties, hotel interiors and rooms by displaying puppet decorations and Banyumas batik motifs, employees inserting Banyumas local language in greeting guests, providing clothing counters and batik decorations in the hotel. Externally, Aston hotel PR cooperates with the local government and tourism office to support maintaining local wisdom.